Paisagem geográfica: muito além do nosso campo de visão - Luis Antonio Bittar Venturi (Confins)
Although understanding Geographical Landscape as “everything that reaches our sight” is largely accepted, this conception cast some doubt on particular methodological matters. Consequently, geographical analysis on the landscape remains narrowed by the conception aforementioned. In order to illustrate these limitations, four counter-arguments to this restricted concept have been raised in this current paper, by showing how each methodological matter can impoverish its understanding. Firstly, the conception of something must target the object itself. Focusing “our sight or field of vision”, the observer is set as the reference point rather than the object to be defined: the landscape itself. Secondly, this traditional definition generates an important issue of scale, which is vital to geographers: if a simple plant or the whole sky reach our sight range, should they be considered landscapes? In other words, what is the landscape size? Is it defined merely by our field of vision? Thirdly, framing the landscape in a field of vision arbitrarily excludes everything that is out of this pictorial perspective. However, many aspects within the frame may be derived from aspects or objects that are out of the frame. Finally, going a little further, many unseen aspects can be inferred by some visible objects. The climate, for instance, which, in turn, can be implied by vegetation, landforms, types of house construction etc. Inferences are possible when we consider landscape as result of a dynamic process, rather than a picture framed by our field of vision. All of these counter-arguments are illustrated along with examples and figures in order to provide better comprehension. Thus, we have featured a conception of landscape that we consider wider, more complete and free from those methodological restrictions formerly shown.